Aplikasi Media Pembelajaran Berbasis Serious Games (Games Education) untuk Belajar Menulis - Nunuk Wahyuningtyas; Normaningsih Normaningsih; Tri Sagirani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
Developing serious games (games education) application for learning media with attention to user experience model for children with special needs becomes an important thing in learning creativity. Through learning of media application, it aims the learning process more interesting and improves learning motivation to raise up the children with Special Educational Needs (SEN), particularly to understand letters, numbers, simple words and learn how to write using the application of learning media and input device (such as pen tablet or touch screen). The utilization of learning media application to the students with special needs would be done through the measurement of User Experience Questionnaire (UEQ), and obtained the excellent value on application appeal, content clarity, efficiency and accuracy, and good value for stimulation and novelty. It can be concluded that the application of learning media based on the serious games for learning media to write can be used as learning tools